The relationship between thyroid autoantibodies and X chromosome monosomy in the chorionic tissue of patients with missed miscarriage - Lu Zhao; Li Liu; Hua Yang (BMC, 2024)
Abstract Objective The aim of this study was to investigate the relationship between thyroid autoantibodies (TGAb and TPOAb) and X chromosome monosomy in the chorionic tissue of patients with missed early miscarriage. Methods The baseline data, thyroid function, thyroid antibody and the chromosomes from the chorionic tissue of 228 patients with missed early miscarriage were examined. Results (1) Among the 228 patients, 121 had a normal chromosome number, and 107 had an abnormal chromosome number. The majority of them were autosomal trisomy, of which trisomy 16 (40.19%) was predominant. Sex chromosome monosomy (28.04%) was secondary. (2) Among the 228 patients, 208 patients in this study had normal thyroid function (including 134 cases of negative thyroid antibodies and 74 cases of positive thyroid antibodies alone); 6 patients had abnormal thyroid function (including 2 cases of clinical hyperthyroidism, 3 cases of subclinical hypothyroidism, 1 case of hypothyroxinemia); and 14 patients had normal TSH and elevated T4 alone.(3) After exclusion of patients with thyroid function abnormalities, there were no significant differences in baseline data between the normal chromosome group and the abnormal chromosome group (P > 0.05). However, there was a significant difference in TGAb and TPOAb between the normal chromosome and abnormal chromosome group with 45, X karyotype, with a higher proportion of TGAb and/or TPOAb positivity in the 45, X karyotype group (P < 0.05). Additionally, compared to TGAb and/or TPOAb-positive patients, the risk of X chromosome monosomy was significantly reduced in TGAb and TPOAb-negative patients (P < 0.05). Moreover, both TGAb and TPOAb titer values in the X chromosome monosomy group were higher than those in the chromosomally normal group (P < 0.05). Conclusion There is a correlation between TGAb, TPOAb and X chromosome monosomy in the chorionic tissue of patients with missed early miscarriage, although the mechanism remains to be further investigated.